Epidemiology of hidradenitis suppurativa in Poland in relation to international data - Matusiak, Łukasz; Kaszuba, Andrzej; Krasowska, Dorota; Placek, Waldemar; Szepietowski, Jacek (Dermatology Review/Przegląd Dermatologiczny, 2017)
Hidradenitis suppurativa (acne inversa) is a chronic, inflammatory, recurrent, debilitating disease of hair follicles manifested by painful, deepseated, inflamed lesions localized in intertriginous areas. Establishing a correct diagnosis seems straightforward enough, as it is based on clinical criteria, but a comparative analysis of published papers on hidradenitis suppurativa epidemiology easily reveals substantial discrepancies in the estimation of the obtained results for the general population. Data on the prevalence of hidradenitis suppurativa in European countries and in the United States of America differ by up to four orders of magnitude, ranging from 0.00033% to 4.1%. Based on data obtained from the Polish National Health Fund and HS reference centres, the prevalence of hidradenitis suppurativa in Poland was estimated at 0.001%, which classifies hidradenitis suppurativa as a rare disease.